High-dose glucocorticoids inducing hyperglycemia in patients with diabetes mellitus experiencing recurrent ischemic stroke attacks: A case report - Fatimatuz Zahro; Tita Sugesti; Siska Hermawati; M. Hari Pristantiningtyas; Herya Putra Dharma; Muhammad Muchlis; Jainuri Erik Pratama; Fauna Herawati; Adji Prayitno; Marisca Evalina Gondokesumo (Jurnal Teknologi Laboratorium)
Stroke is an acute and focal neurological syndrome characterized by clinical deficits resulting from vascular injuries such as infarction or hemorrhage in the central nervous system. Given the prevalence of multiple comorbidities among stroke patients, they often find themselves on more than five medications, falling into the category of polypharmacy. Beyond treatments aimed at improving stroke outcomes and managing comorbid conditions, the presence of additional diseases may necessitate new therapies, potentially leading to side effects that can intersect and exacerbate the existing disease. This case report aims to present instances of hyperglycemia in stroke patients undergoing high-dose glucocorticoid therapy and discuss potential strategies to address this issue. In this particular case, human insulin was selected to rapidly control the patient's hyperglycemic condition. Subsequently, adjustments to basal and bolus insulin doses were made based on the frequency of use and duration of action of the glucocorticoid, specifically methylprednisolone. In conclusion, the hyperglycemia induced by glucocorticoids was identified through postprandial sugar monitoring, necessitating treatment through modifications to basal and bolus insulin doses. Strategies for managing hyperglycemia should be tailored to the pharmacokinetics of glucocorticoids and insulin.